The philosophy of Popper - Burke, T. E. (Manchester, UK ; Dover, N.H., USA : Manchester University Press, 1983)
Sir Karl Raimund Popper (28 July 1902 -17 September 1994) was an Austro-British philosopher and professor at the London School of Economics. He is generally regarded as one of the greatest philosophers of science of the 20th century. He also wrote extensively on social and political philosophy. [...] Popper is known for his attempt to repudiate the classical observationalist/Inductivist form of scientific method in favour of empirical falsification. He is also known for his opposition to the classical justificationist account of knowledge which he replaced with critical rationalism, "the first non justificational philosophy of criticism in the history of philosophy". In political discourse, he is known for his vigorous defence of liberal democracy and the principles of social criticism that he came to believe made a flourishing "open society" possible. -- From http://en.wikipedia.org (Sep. 7, 2012).
1. The philosophy of philosophy --- 2. The philosophy of science --- 3. Relativism and truth --- 4. Historicism --- 5. Freedom and values.
Includes bibliographical references (p. [217]-218) and index.
Keywords: Popper, Karl R. -- 1902-1994.; Philosophers -- Great Britain -- Bibliography; Rationalism; Philosophy